Real-time observation of template-assisted colloidal aggregation and colloidal dispersion under an alternating electric field - 李超荣 李书文 梅洁 徐庆 郑莹莹 董文钧 (Chinese physics B, 2011)
A fascinating colloid phenomenon was observed in a specially designed template-assisted cell under an alternating electrical field. Most colloidal particles experienced the processes of aggregation, dispersion and climbing up to the plateaus of the patterns pre-lithographed on the indium tin oxide glass as the frequency of the alternating electrical field increased. Two critical frequencies fcritl ≈ 15 kHz and fcrit2 ≈ 40 kHz, corresponding to the transitions of the colloid behaviour were observed. When f 〈 15 kHz, the particles were forced to aggregate along the grooves of the negative photoresist patterned template. When 15 kHz 〈 f 〈 40 kHz, the particle clusters became unstable and most particles started to disperse and were blocked by the fringes of the negative photoresist patterns. As the frequency increased to above 40 kHz, the majority of particles started to climb up to the plateaus of the patterns. Furthermore, the dynamics analysis for the behaviour of the colloids was given and we found out that positive or negative dielectrophoresis force, electrohydrodynamic force, particle-particle interactions and Brownian motion change with the frequency of the alternating electric field. Thus, changes of the related forces affect or control the behaviour of the colloids.